Envisioning the Future of Online Learning [electronic resource] : Selected Papers from the International Conference on e-Learning 2015 - Luaran, Johan Eddy.; Sardi, Janudin; Aziz, Anealka; Alias, Nor Aziah; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2016)
This book shares insights into the various ways technology can be used for educational purposes, utilizing an approach suitable for both novice and advanced practitioners in this niche area. It features selected papers presented at the International Conference on e-Learning 2015 (ICeL 2015), where professionals discussed how technology can not only serve as a tool in the classroom, but as the classroom itself. As the title ?Envisioning the Future of Online Learning? suggests, this book showcases current best practices in the field of e-learning, where technology has been leveraged to re-engineer the landscape of education, particularly in the context of Malaysia.
1 iPad-agogy: Expanding or Limiting Pedagogical Skills? -- 2 Understanding Teacher Educators' Belief and Use of Information and Communication Technologies in Teacher Training Institute -- 3 Employing Websites in Language Learning for Tourism Purpose among Arabic Learners at the MARA Poly-Tech College (KPTM) -- 4 The Nature of Student Group Online Interactions in Learning ICT Education -- 5 Designing a Collaborative Malaysian-Vietnamese Online Writing Project: A Design-Based Research -- 6 Assessing User Needs Analysis for Inter-School Social Information Sharing Portal -- 7 Feel-It: An Intelligent Secondary School Physics Q&A System -- 8 Conceptualizing Data Driven Decision Support Component in Academic Information Management System -- 9 Inter-School Information Sharing Activities through Cloud Services: User Willingess and Less Favored Areas -- 10 An Interactive Approach of an E-Tajweed Yaasin System -- 11 An Empirical Study: Learning Programming using eLearning -- 12 A Case Study in developing the ICT skills for a group of Mixed Abilities and Mixed Aged Learners at ITEP in Dubai-UAE and Possible Future RFID Implementations -- 13 A Study of Students' Interaction in Edmodo Social Networking Platform -- 14 An Analysis of Organizational Dimension as Predictor to the Intention to use of e-Training System among Senior School Administrators -- 15 Interactive Visual Art Education Pedagogical Module: Typography in Visual Communication -- 16 MOOC at Universiti Sains Malaysia: Factors impacting the teaching and learning outcomes of TITAS Course -- 17 Measuring the effectiveness of courseware content using learning theory for a Programming subject -- 18 Blended Learning Mode: An Analysis of the Practices among UiTM Pahang Lecturers -- 19 Students' perceptions of Blended learning and achievement -- 20 Identification of Social Presence for E-learning: An Initial Multiphase Activities for Requirements Engineering -- 21 Peridontal Risk Assessment Application for the Usage in Dental Clinic -- 22 Students' perceptions of New Web 2.0 Tools' Usage in Classroom Instruction -- 23 Utilising Twitter for promoting Active Learning in Teaching and Learning -- 24 Towards envisioning the future of learning in Malaysia: Development of a Malaysia MOOC based on the Iterative ADDIE Model -- 25 Google Forms for Students' and Teachers' Self Reflection Practices -- 26 Visual Thinking Courseware (VTC): Enhancing critical thinking skills among spatial learners -- 27 Investigating the usefulness of Blended Learning: A Case of UiTM Negeri Sembilan -- 28 Mobile Learning, Effective Integration of New Technologies into Existing Models -- 29 Technology factors that drive Students' knowledge sharing ability in Online Discussion Interface: The Conceptual Model -- 30 Measuring User's Usage Intentions on e-Learning Portal -- 31 Providing a Mobile Service for Academics and Professionals: Need Analysis for the Development of Mobile App Glossary of Terms in Islamic Banking and Finance -- 32 Smoking Cessation: Learning through App Development -- 33 A comparative study of Single Maker Based and Multiple Touch Functions for Visualizing Engineering Contents -- 34 Interactive Prophet's Storybook using Augmented Reality -- 35 Blazing a trail for Global Access Asia -- 36 E-learning perception and language proficiency among selected diploma and degree students in a Malaysian University -- 37 Mobile phone app insights: L-Listen, I-Interact, R-Reflect, A-Act (LIRA) -- 38 A conceptual framework for Online Training Effectiveness in Malaysian Public Sectors -- 39 Development of a One Stop Distance Virtual Learning (DVL) Program for Diploma of Pharmacy Students during hospital attachment -- 40 Learning beyond the Walls: The role of WhatsApp groups -- 41 Creating enhancement activities using a Game Template.
Keywords: Education; Educational technology; Education